Decisions at Perryville : the twenty-two critical decisions that defined the battle - Peterson, Larry (Command decisions in America's Civil War, 2022)
"The Battle of Perryville was the culmination of the Confederate Heartland Offensive as General Braxton Bragg's army won a strategic victory over Major General Don Carlos Buell's corps from the Union Army of the Ohio. However, as Bragg retreated into Tennessee shortly after the battle, he effectively granted control of Kentucky to the Union, and the North would hold this critical border state for the remainder of the American Civil War. In Decisions at Perryville, Larry Peterson examines the critical decisions that shaped the way the battle unfolded. Rather than offering a history of the battle, Peterson focuses on the critical decisions confronting Federal and Confederate leaders and ultimately shaping the battle as we know it today"--